Mycoflora and natural occurrance mycotoxins in corn, soybean meal and wheat pollard in Malaysia - Shazali, Nurhazirah; Loh, Teck Chwen; Foo, Hooi Ling; Akit, Henny; Kamalludin, M. H. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
The purpose of this study was to identify the mycoflora and mycotoxins production in corn, soybean meal and wheat pollard in Malaysia. The study demonstrated that corn had significantly higher mycoflora counts as compared to other grains. Corn, wheat pollard and soybean meal contained at least one of the main mycotoxigenic genera such as Aspergillus spp., Penicillium spp., and Fusarium spp. and the most toxicogenic fungi (15.4% to 75%). All raw materials were contaminated with fungus and mycotoxins have been detected with a various concentration of aflatoxins (AF), ochratoxin A (OTA), zearalenone (ZEA), and deoxynivalenol (DON). Overall results show that corn, soybean meal and wheat pollard contained a higher concentration of AFB2, DON and ZEA contamination. As conclusion, the presence of fungi and mycotoxins indicates the existence of contamination.